Classical conditioning in borderline personality disorder: an fMRI study - Krause-Utz, Annegret; Bohus, Martin; Schmahl, Christian (European archives of psychiatry and clinical neuroscience, 2016)
Previous research suggests disturbed emotional learning and memory in borderline personality disorder (BPD). Studies investigating the neural correlates of aversive differential delay conditioning in BPD are currently lacking. We aimed to investigate acquisition, within-session extinction, between-session extinction recall, and reacquisition. We expected increased activation in the insula, amygdala, and anterior cingulate, and decreased prefrontal activation in BPD patients. During functional magnetic resonance imaging, 27 medication-free female BPD patients and 26 female healthy controls (HC) performed a differential delay aversive conditioning paradigm. An electric shock served as unconditioned stimulus, two neutral pictures as conditioned stimuli (CS+/CS-). Dependent variables were blood-oxygen-level-dependent response, skin conductance response (SCR), and subjective ratings (valence, arousal). No significant between-group differences in brain activation were found [all p(FDR) > 0.05]. Within-group comparisons for CS+unpaired > CS- revealed increased insula activity in BPD patients but not in HC during early acquisition; during late acquisition, both groups recruited fronto-parietal areas [p(FDR) < 0.05]. During extinction, BPD patients rated both CS+ and CS- as significantly more arousing and aversive than HC and activated the amygdala in response to CS+. In contrast, HC showed increased prefrontal activity in response to CS+ > CS during extinction. During extinction recall, there was a trend for stronger SCR to CS+ > CS in BPD patients. Amygdala habituation to CS+paired (CS+ in temporal contingency with the aversive event) during acquisition was found in HC but not in patients. Our findings suggest altered temporal response patterns in terms of increased vigilance already during early acquisition and delayed extinction processes in individuals with BPD.